Предмет: Алгебра,
автор: Jens123
Упростите выражение
a) -3x(2-x)+(3x+1)(x-2)
б) 3(2x-1)²+12x
в) (x+3)²-(x-2)(x+2)
Ответы
Автор ответа:
0
а) -6х + 3x^2 + 3x^2 - 6x + x - 2= -11x+6x^2-2=(x-2)(x-1/6)
б) 3(4x^2-4x+1)+12x=12x^2+3-12x+12x=12x^2+3
в) x^2+6x+9-(x^2-4)=x^2+6x+9-x^2+4=6x+13
б) 3(4x^2-4x+1)+12x=12x^2+3-12x+12x=12x^2+3
в) x^2+6x+9-(x^2-4)=x^2+6x+9-x^2+4=6x+13
Автор ответа:
0
а) -6х + 3х^2 + 3х^2 - 6х - 2 = 6х^2 - 12х = 6х(х-2)
б) 3(4х^2 - 4х + 1) +12х = 12х^2 - 12х + 3 (можно решить квадратное уравнение и найти х)
в) х^2 + 6х +9 - (х^2 -2х -4 + 2х) = х^2 + 6х + 9 -х^2 + 2х + 4 - 2х = 6х + 13
Вроде так...
Что-то не так сделала?..
б) 3(4х^2 - 4х + 1) +12х = 12х^2 - 12х + 3 (можно решить квадратное уравнение и найти х)
в) х^2 + 6х +9 - (х^2 -2х -4 + 2х) = х^2 + 6х + 9 -х^2 + 2х + 4 - 2х = 6х + 13
Вроде так...
Что-то не так сделала?..
Похожие вопросы
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Қазақ тiлi,
автор: Sake228
Предмет: Алгебра,
автор: ajzanismailova13
Предмет: Физика,
автор: vstaritsyn2014
Предмет: История,
автор: dzyaniska96